Association of early discharge and clinical outcomes following proctectomy for patients with rectal cancer: A NRD analysis - Aboubacar Cherif; Troy N. Coaston; Melissa Justo; Dariush Yalzadeh; Saad Mallick; Zihan Gao; Esteban Aguayo; Peyman Benharash; Hanjoo Lee (PLoS ONE, 2026)
Background Adoption of enhanced recovery pathways in proctectomy has gained attention due to its potential to reduce resource utilization and optimize recovery. Using a nationally representative cohort, we examined the association between early discharge (within 3 days) and 30-day readmissions, perioperative complications, and hospitalization costs. Methods Adult (≥18 years) patients with rectal cancer undergoing proctectomy were identified using the 2016–2021 Nationwide Readmissions Database. Patients were classified as Early if they were discharged within 3 days of proctectomy and otherwise were classified as Routine. Multivariable regression models were developed to assess associations between early discharge and 30-day outcomes, as well as associated readmission, costs, and mortality. Entropy balancing was employed to obtain a weighted comparison to adjust for intergroup differences. Results Of an estimated 39,505 patients, 25.8% were discharged early. Early was younger (59 [51−68] vs 62 years [53−71], p < 0.001), had lower comorbidity burden (2 [1 –3] vs. 3 [2 –4] unit, p < 0.001), and more frequently received laparoscopic proctectomy (60.9 vs. 39.0%, p < 0.001). Following entropy balancing, early discharge was associated with lower readmission rates (adjusted odds ratio [AOR], 0.77; 95% confidence interval [CI], 0.69–0.86) and decreased cumulative hospitalization costs (β: − $6.2K; 95% CI, − 8.6k to −3.7k). Mortality at readmission was similar between the two groups (AOR, 0.69; 95% CI, 0.33–1.45). Conclusions Early discharge after proctectomy is feasible for rectal cancer patients when clinically appropriate and is associated with reduced readmissions and hospitalization costs without compromising patient safety compared to routine. Broader implementation of early discharge protocols may optimize outcomes for rectal cancer patients undergoing proctectomy.